Low temperature synthesis of spindle‐like ZnO nanostructures under microwave irradiation. Issue 11 (1st October 2013) - Ji, Zhenyuan; Sun, Jiquan; Shen, Xiaoping; Zhu, Guoxing
<x xml:space="preserve">Abstract</x> A simple and general microwave route is developed to synthesize nanostructured ZnO using Zn(acac)2·H2O (acac = acetylacetonate) as a single source precursor. The reaction time has a great influence on the morphology of the ZnO nanostructures and an interesting spindle‐like nanostructure is obtained. The microstructure and morphology of the synthesized materials are investigated by X‐ray diffraction (XRD), scanning electron microscopy (SEM), field‐emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), high‐resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED). It is found that all of them with hexagonal wurtzite phase are of single crystalline structure in nature. Ultraviolet–visible (UV‐vis) absorption spectra of these ZnO nanostructures are investigated and a possible formation mechanism for the spindle‐like ZnO nanostructures is also proposed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>